"A thing studied and rehearsed": Ben Jonson in Parts. (1st October 2016) - Boguszak, Jakub
ABSTRACT: Shakespeare has emerged as a dramatist who could make good use of his first-hand experience with acting and actors' part-scripts, a playwright willing to experiment and challenge (as well as guide) his actors through their parts. This article turns to Ben Jonson, Shakespeare's friend and colleague, who was also well acquainted with the actors who performed his plays and who also, in fact, was once an actor himself. It shows that many of Jonson's parts can be safely reconstructed from the early printed editions, as there are good reasons to question the general opinion which sees all Jonson's publications as texts carefully revised and rewritten for the literate audience. Having established the reliability of the surviving texts, the article proceeds to consider some of Ben Jonson's individual parts. It shows how Jonson's parts manage to convey humours, what kinds of information they provide to, and withhold from, actors, and how they relate comic moments. The stock type of a Jonsonian rogue is introduced as a useful case study. The conclusion points out affinities between some of Shakespeare's and Jonson's parts and uses them to question the power of early modern theatre to promote any one author's singular voice.